Farewell of the editor of the Journal of High Andean Research - Escobar-Mamani, Fortunato (2022)
The purpose of this editorial is to present a brief reflection on my work as the editor-in-chief of the Revista de Investigaciones Altoandinas - Journal of High Andean Research, which I have directed for nearly 10 years. With gratitude, I try to highlight the achievements and bring to light the weaknesses and what is still pending. This is in line with the ethical code of scientific publications developed by the Committee on Publication Ethics (COPE). From now on a new editor-in-chief and editorial board is to direct the future development of the journal.